Diagnostic biomarkers from proteomic characterization of cerebrospinal fluid in patients with brain malignancies. Issue 2 (9th April 2021) - Schmid, Dominic; Warnken, Uwe; Latzer, Pauline; Hoffmann, Dirk C.; Roth, Judith; Kutschmann, Stefanie; Jaschonek, Hannah; Rübmann, Petra; Foltyn, Martha; Vollmuth, Philipp; Winkler, Frank; Seliger, Corinna; et al.
Abstract: Recent technological advances in molecular diagnostics through liquid biopsies hold the promise to repetitively monitor tumor evolution and treatment response of brain malignancies without the need of invasive surgical tissue accrual. Here, we implemented a mass spectrometry‐based protein analysis pipeline which identified hundreds of proteins in 251 cerebrospinal fluid (CSF) samples from patients with four types of brain malignancies (glioblastoma, lymphoma, brain metastasis, and leptomeningeal disease [LMD]) and from healthy individuals with a focus on glioblastoma in a retrospective and confirmatory prospective observational study. CSF proteome deregulation via disruption of the blood brain barrier appeared to be largely conserved across brain tumor entities. CSF analysis of glioblastoma patients identified two proteomic clusters that correlated with tumor size and patient survival. By integrating CSF data with proteomic analyses of matching glioblastoma tumor tissue and primary glioblastoma cells, we identified potential CSF biomarkers for glioblastoma, in particular chitinase‐3‐like protein 1 (CHI3L1) and glial fibrillary acidic protein (GFAP). Key findings were validated in a prospective cohort consisting of 35 glioma patients. Finally, in LMD patients who frequently undergo repeated CSF work‐up, we explored our proteomic pipeline as a mean to profile consecutive CSF samples. Therefore, proteomic analysis of CSF in brain malignancies has the potential to reveal biomarkers for diagnosis and therapy monitoring. Abstract : Cerebrospinal Fluid (CSF) offers an avenue for molecular follow up of brain malignancies to tailor treatments to individual patients. In this study, mass spectrometry is applied to characterize the CSF proteome of 251 brain tumor patients and controls, revealing tentative glioblastoma CSF markers such as chitinase‐3‐like protein 1 and glial fibrillary acidic protein, but also highlighting the distortion of the CSF proteome by blood‐brain barrier disruption. Proteomic signatures in two glioblastoma cohorts are associated with changes in overall survival. Therefore, technically demanding CSF proteomics are feasible and should be applied to larger prospective patient cohorts to find clinically actionable biomarkers.